2021
DOI: 10.3390/jpm11010049
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Screening Identifies Individuals at High Risk for Hereditary Transthyretin Amyloidosis

Abstract: The TTR V142I variant associated with hereditary transthyretin amyloidosis (hATTR) is present in up to 4% of African American (AA) and 1% of Hispanic/Latinx (HL) individuals and increases risk for heart failure. Delayed and missed diagnoses could potentiate health disparities in these populations. We evaluated whether population-based genomic screening could effectively identify individuals at risk for hATTR and prompt initiation of risk management. We identified participants of the BioMe Biobank in New York C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Other approaches have also been proposed. In 2021, Birnbaum et al ( 20 ) and Ingoe et al ( 23 ) demonstrated increased diagnosis of FH and utilization of genetic testing after system-wide scanning of the EHR to identify patients at high risk; and Soper et al ( 59 ) described a genomic screening program that identified individuals with variants in TTR , none of whom had a previous diagnosis of hereditary transthyretin amyloidosis. Adopting implementation science frameworks and practices may also facilitate the uptake of guideline-directed genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches have also been proposed. In 2021, Birnbaum et al ( 20 ) and Ingoe et al ( 23 ) demonstrated increased diagnosis of FH and utilization of genetic testing after system-wide scanning of the EHR to identify patients at high risk; and Soper et al ( 59 ) described a genomic screening program that identified individuals with variants in TTR , none of whom had a previous diagnosis of hereditary transthyretin amyloidosis. Adopting implementation science frameworks and practices may also facilitate the uptake of guideline-directed genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…This was not a systematic review, nor was a formal quality appraisal of studies conducted. Moreover, this review was limited to Tier 1 conditions-future research and evidence synthesis will be needed to address other actionable gene-condition pairs (e.g., other genes for hereditary breast and ovarian cancer including PALB2, RAD51C, RAD51D, and BRIP1 ( Manchanda et al, 2018 ); TTR for hereditary transthyretin amyloidosis ( Soper et al, 2021 ); endocrine tumour genes ( Savatt et al, 2022 ); arrhythmia syndrome genes ( Walsh et al, 2022 )) and their suitability for population genomic screening.…”
Section: Limitationsmentioning
confidence: 99%
“…The advent of more widespread genetic testing facilitated by next-generation DNA sequencing technologies presents new opportunities to potentially redefine our understanding and approach to hATTR diagnosis and treatment. Identifying individuals at risk through systematic screening for genomic variants in TTR , rather than symptom-based clinical ascertainment, could both clarify the true scope of the disease at a population scale and enable earlier intervention to potentially mitigate disease progression and thereby improve outcomes ( 5 ). Because hATTR cardiomyopathy is generally only clinically recognized once profound ventricular remodeling and dysfunction are present these opportunities for improving outcomes may be substantial, particularly in light of newly approved treatments ( 1 , 6 ).…”
mentioning
confidence: 99%